Pengembangan Model Missouri Mathematic Project Berbantuan Microsoft Math Solver terhadap Kemampuan Berpikir Kritis Matematis - Setyawati, Ririen; Simamora, Yumira; Fatmah Syarah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study was to determine the validity, effectiveness, and efficiency of the Missouri Mathematics Project model, supported by Microsoft Math Solver, for students' mathematical critical thinking skills. The study used the ADIIE model, with a sample of 30 students from grade X-3 at Bina Bersaudra School. The results showed that the classical learning outcomes achieved in the final trial were 76.6%, categorized as high, meeting the classical learning outcomes desired by the researcher. The final trial student response questionnaire score was 86.3%. The validator declared the MMP learning model and the developed learning instruments feasible based on all validity aspects, categorized as valid. The conclusion is that student responses are very effective for mathematical critical thinking skills. Practicality in mathematics learning, with an average score of 96.6%, categorized as very practical in the mathematics learning process. Keywords: Mathematical Critical Thinking, Microsoft Math Solver, Missouri Mathematics Project Model